1997
DOI: 10.1021/bi971730v
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Activity of Protein C by Mutagenesis To Improve the Membrane-Binding Site:  Studies Related to Proline-10

Abstract: Bovine and human protein C show high homology in the amino acids of their GLA domains (amino-terminal 44 residues), despite the about 10-fold higher membrane affinity of the human protein. A proposed membrane contact site and mechanism suggested that this difference was largely due to the presence of proline at position 10 of bovine protein C versus histidine at position 10 of human protein C [McDonald, J.F., Shah, A.M., Schwalbe, R.A., Kisiel, W., Dahlback, B., and Nelsestuen, G.L. (1997) Biochemistry, 36, 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 41 publications
3
51
0
Order By: Relevance
“…Human ␣-thrombin was from Haematologic Technologies, Inc. (Essex Junction, VT). Recombinant human wild-type protein C was expressed, isolated, and activated as described (37), and the APC concentration was determined by chromogenic substrate S2366. Human protein S was purified as reported (38) with minor modifications, as described (39).…”
Section: Methodsmentioning
confidence: 99%
“…Human ␣-thrombin was from Haematologic Technologies, Inc. (Essex Junction, VT). Recombinant human wild-type protein C was expressed, isolated, and activated as described (37), and the APC concentration was determined by chromogenic substrate S2366. Human protein S was purified as reported (38) with minor modifications, as described (39).…”
Section: Methodsmentioning
confidence: 99%
“…6 We have previously reported that site-directed mutagenesis of positions 10 to 12, 32, and 33 in protein C result in protein C variants with enhanced membranebinding ability and anticoagulant activity. 7,8 We now report on novel Gla domain mutations resulting in the creation of APC variants with very high anticoagulant activity. The results provide insights into the link between sequence variations of the Gla domain and the membrane-binding properties and the importance of membrane binding for expression of APC anticoagulant activity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion has been supported by mutations of the Gla domain that affect membrane affinity. For example, the P10H mutant of bovine protein C shows an ϳ10-fold enhancement in membrane affinity, whereas the H10P mutant of human protein C shows an ϳ3-fold decline in membrane affinity (9). Although a major difference among the vitamin K-dependent proteins is a Gla residue versus another amino acid at position 32, the Q32E mutation of protein C has no impact on membrane affinity (10,11).…”
mentioning
confidence: 99%